BLUEPRINT FOR A SUSTAINABLE BLUE ECONOMY: CHALLENGES, OPPORTUNITIES, AND POLICY PATHWAYS - Kamal un Nabi; Mohsina Hayat (EP FEB UNS, 2025)
The Blue Economy has emerged as a crucial paradigm for achieving sustainable economic growth, environmental conservation, and social equity through the responsible utilization of marine resources. This study explores the multifaceted dimensions of the Blue Economy, highlighting its potential across key sectors such as fisheries, aquaculture, maritime transport, renewable energy, and marine biotechnology. India's strategic maritime position, coupled with initiatives like the Deep Ocean Mission and Pradhan Mantri Matsya Sampada Yojana, underscores its commitment to integrating ocean-based economic activities with global sustainability goals, particularly Sustainable Development Goal 14. Despite its vast potential, challenges such as overfishing, marine pollution, habitat degradation, and climate change threaten the sustainable advancement of the Blue Economy. However, opportunities exist in expanding aquaculture, developing marine-based renewable energy, and promoting ecotourism. The study underscores the importance of adaptive governance, technological innovation, and community-driven approaches to overcome these challenges. Through an empirical analysis incorporating correlation and regression models, the study establishes significant linkages between sustainable marine practices, economic growth, and livelihood enhancement. The findings emphasize that fostering a resilient Blue Economy requires a multi-pronged strategy encompassing inclusive policies, innovative financing mechanisms, and cross-sectoral collaboration. By aligning economic incentives with marine conservation efforts, the Blue Economy can serve as a transformative model for achieving long-term environmental and economic sustainability.